Aurora Cáceres´ Personal Scrapbook (1880-1925) in Datasets: a Theoretical, Critical and Methodological Approach for Analyzing the Sociocultural Practices of turn of the century (1880-1925) Latin American Women Intellectuals, from the Field of Digital Huma - Arakaki, Mónica (2024)
We analyze Aurora Cáceres´ (1872-1958) personal scrapbook from a perspective grounded on the tenets of digital humanities and information science. By converting it into datasets, we aim to make machine readable such a complex and heterogeneous object, and also, comprehensively approachable, without ignoring the semantic complexity of the objects´ diverse materialities. We aim to overcome the traditional consideration of such complex devices as sources for extracting isolated information or limited to intimate and apolitical spheres. With her personal scrapbook, Cáceres, like other women intellectuals from her time, showcases her political agency, as well as the strategies deployed in order to build a history and memoir in which she has got a leading role. Moreover, having been released as open, the datasets can be profited from by other researchers worldwide. Therefore, this work aims to be a methodological contribution for the study of such heterogeneous sources, which are frequently bypassed or minimized because of the challenges they pose to conventional systems of understanding, classification and preservation.